(3JgPjH GdUMGMs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3MSjf Hf MSf Hf Ydi Hf CMeO Hf eMeO GdOeQi GdeMdi GdeGdci s)
(3ChdgG (B:s
(3cJGH GdUMGM ddEeGe GdLhgQi QMeg Gddg , ai Yde dZI GdYQH hdjS gh CUd eDdag ef cd hLg s
(3BNQgG (B:s
(3hPgHJ GdCda GdJi ai jG dGLJeGY GdSGcfjf bGd Ph GdQeI (B: (3CdG jG CSdei jG OGQei Ydi GdHdi hdG RGd efgdkG HLQYGFdg GdbWQ Je cJGH GdUMGM s
(3HgG CKQ QWhHI hfbY eGAs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
Keywords: (3GddZIs